Secure distribution and access of XML documents. (3rd April 2006) - Zhang, Junqi; Varadharajan, Vijay; Mu, Yi
XML has been widely used for representation and storage of documents and their exchange over the internet. Security mechanisms for the protection of XML document sources and their distribution are essential. In this paper, we present a novel scheme for securing XML documents and their distribution over the internet. The proposed scheme has some distinct features. It requires only one private key for each user. Therefore, when a user leaves or joins the system, keys of all the other existing users in the system remain unchanged. This makes the proposed scheme more attractive, and hence particularly suitable for the dynamic distribution of documents over the internet.